Heat Transfer Analysis in a Channel Mounted with In-Line Downward-Facing and Staggered Downward-Facing Notched Baffles - Arnut Phila; W. Keaitnukul; Manoj Kumar; Monsak Pimsarn; S. Chokphoemphun; Smith Eiamsa–ard (Eng—Advances in Engineering, 2025)
This study presents a comprehensive analysis of heat transfer enhancement, flow resistance, and thermal performance in rectangular channels equipped with three baffle configurations: conventional transverse baffles (TBs), in-line downward-facing notched baffles (IDF-NBs), and staggered downward-facing notched baffles (SDF-NBs). The influence of the pitch-to-baffle height ratio (P/e), ranging from 2.0 to 10, was examined across Reynolds numbers from 6000 to 24,000. Results indicate that a P/e ratio of 6.0 consistently yielded the highest Nusselt numbers across all configurations. While the TB configuration produced significant heat transfer at P/e= 6.0, it experienced a substantial friction penalty, with its best thermal enhancement factor (TEF = 1.168) observed at P/e = 8.0. The IDF-NB configuration achieved optimal performance at P/e = 6.0 with a TEF of 1.257, offering a better balance between heat transfer and flow resistance. The SDF-NB arrangement outperformed all other cases, delivering the highest Nusselt number (Nu = 116.9), TEF (1.362), and improved flow reattachment, primarily due to enhanced mixing from the staggered layout. These findings demonstrate that the staggered notched baffle configuration at P/e = 6.0 offers the most effective thermal performance enhancement among the configurations studied.
Keywords: Heat Transfer Mechanisms; Nanofluid Flow and Heat Transfer; Heat Transfer and Optimization